Etude De L’évolution Du Trait De Côte À L’aide De L’outil Mobitc : Cas Du Littoral De Grand-Bassam - Touré Mamadou; Ané Niamien Jean N.; Tiémélé Jacques André; Kassi A. Jean-Baptiste; Djagoua Eric M. Valère (European Scientific Journal, ESJ, 2018)
This study proposes an assessment of the historical coastline (TDC) mobility of the Ivorian coastline, specifically the Grand-Bassam coastline (Côte d'Ivoire), and suggests reflections on the sustainable management of the coastal environment in Côte d'Ivoire, taking into account coastal erosion. The objective is to evaluate, using the MobiTC software, the spatio-temporal and statistical evolution of the morphology of the Grand-Bassam coastal zone in order to plan appropriate coastal developments. Specifically, it is to extract images on google earth, to treat them under MobiTC and to analyze the rate of spatio-temporary and statistical evolution of coastlines. To do this, data from QuickBird images provided by Google Earth from 1984, 1988, 1992, 1996, 2000, 2004, 2008, 2012 and 2016 in the study area were used. Different software was used for image processing. The ENVI 5.1 software allowed georeferencing and thresholding to make the images superimposable and highlight the baseline. The digitization of the images was done with ArcGis software. The QGIS 2.18 software was used to convert the .shp files to the mid / mif format of the MobiTC software. The latter makes it possible to understand the statistical evolution of the coastline dynamics from the creation of a baseline, the skeleton of envelopes and traces. The variations observed between 1984 and 2016 show a fattening of 0.23 m / year in some sectors and an erosion rate of 0.34 m / year in other sectors. It is noted that 62.79% of the coastline is accretion and 37.21% is eroding.